Decision making in the treatment of class III furcation: resective therapy? Extraction? Implant? - Antonio Wilson Sallum; Enilson Antonio Sallum; Francisco Humberto Nociti Júnior; Renato Corrêa Viana Casarin; Fernanda Vieira Ribeiro; Márcio Zaffalon Casati
The presence of furcation lesions is associated with bone resorption and lack of insertion in the inter-radicular space, and is a condition that considerably increases the risk of dental loss, particularly in the absence of adequate treatment. In this context, the object of some of the therapies is to keep teeth with furcation lesions that are important to dental planning, to re-establish an anatomy that enables the patient to remove dental biofilm from the compromised area. However, the long term maintenance and treatment of molars with Class III furcation lesions continues to be a challenge to dentists during periodontal therapy, since the anatomy of the inter-radicular region makes it difficult for both professionals and patients to gain access to perform adequate and efficient control of dental biofilm. The impossibility of obtaining appropriate decontamination of the area involved during the root scraping process, including by means of surgical access, demands thatdentists have adequate knowledge to determine the correct therapeutic approach during the treatment of teeth with advance inter-radicularbone loss. The aim of the present study was to discuss the treatments available for Class III furcation lesions and relate clinical procedures that could be performed for the treatment of this type of defect.